KARAKTERISTIK DAY SPA DI KECAMATAN KUTA SELATAN, BALI - Darmawijaya, I Gede; Sekarti, Ni Ketut (JURNAL KEPARIWISATAAN, 2011)
Spa industry is a fast growing industry in the world as well as in Bali. The annual average growth of numbers of day spas in this area is 40% since 1995. This research was aim at revealing the characteristics of day spa in the Kuta, Bali. Data were collected from 50 day spas. The instrument used is questionnaire foÂcusing on spa business model, spa facilities, spa treatment, spa treatment price and spa human resources. The findings of this research were: spa business model were mostly non-franchise; the annual growth was 40%; average business hours was 13 hours; average area was 1012 m2; average number of treatment room was 8,56 rooms; average number of manicure and pedicure room and other spa facilities were less than one; the most to the least popular massage were Balinese massage, aromatherapy massage, and Shiatsu massage; the cheapest price of treatment per hour was Rp 40.000 and the highest price was Rp 650.000; perÂcentage of male and female employees were 14% and 86%; employees with comÂpetencies certificate is 1,2%; educational background of employees were 5% undergraduate, 8% associate degree, 86% senior high school, and 1 % junior high school.